?RELATIONSHIPS BETWEEN HEAVY METAL CONTENT AND BODY WEIGHT OF SELECTED FRESHWATER FISH SPECIES OF THE LOWER IKPOBA RIVER IN BENIN CITY, NIGERIA (Biological Sciences - PJSIR, 2003)
The relationships between the heavy metals content and body weight of edible muscle of selected freshwater fish species of the lower Ikpoba river in Benin City Nigeria, were studied using the atomic absorption spectrophoto- metry technique. 27 samples of Clarias gariepinus (average wt: 110.80 ± 36.31g); 36 samples of Channa obscura (average wt: 65.20 ± 27.20g) and 18 samples of Chromidotilapia guentheri (average wt: 80.10 ± 31.70g) were used for the study. Mean heavy metals concentration (?g/g dry wt.) varied from Cd (0.02 ± 0.01), through Cu (0.25±0.07), Pb (0.40 ± 0.60) to Zn (6.0 ± 1.03) in Clarias gariepinus and through Cd (0.02 ± 0.03), Cu (0.04 ± 0.02), Pb (0.27 ± 0.05) to Zn (2.10 ± 0.02) in Channa obscura and through Cd (0.02 ± 0.05), Cu (0.30 ± 0.05), Pb (0.40 ± 0.2) to Zn (6.15 ± 1.70) in Chromidotilapia guentheri. Relatively low metal values were recorded in Channa obscura. Significant correlations were recorded between cadmium, lead, zinc and copper and body weight of Clarias gariepinus and Chromidotilapia guentheri (P < 0.05). However, in the predatory Channa obscura, statistical analysis showed that copper and zinc contents were significantly correlated while cadmium and lead were not (P > 0.05).